2020
DOI: 10.1002/jlb.3mr0120-390r
|View full text |Cite
|
Sign up to set email alerts
|

Eosinophils in wound healing and epithelial remodeling: Is coagulation a missing link?

Abstract: Eosinophils are often cited as playing roles in wound healing and epithelial remodeling; however, the exact triggers and mechanisms of such activity remain poorly understood. Eosinophils show the remarkable capacity to partner with coagulation, which is a highly conserved biologic system evolved to protect an organism from injury by promoting hemostasis and tissue repair. Eosinophils contribute directly by producing key factors in coagulation (tissue factor, thrombin) and fibrinolysis (plasminogen). Moreover, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 144 publications
2
32
0
Order By: Relevance
“…Additionally, antibody formation by lymphocytes has been shown to significantly increase fibroblast proliferation and decrease apoptosis in the wound bed and edges [ 32 ]. Recently, eosinophils have been described as important regulators of local immunity and remodeling/repair in both health and disease, showing that eosinophils can downregulate inflammation and repair damaged tissue as well [ 33 ]. The study of the responses of this type of cells is therefore relevant in order to understand the effects of modulating agents on basic cellular biology in the wound healing process.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, antibody formation by lymphocytes has been shown to significantly increase fibroblast proliferation and decrease apoptosis in the wound bed and edges [ 32 ]. Recently, eosinophils have been described as important regulators of local immunity and remodeling/repair in both health and disease, showing that eosinophils can downregulate inflammation and repair damaged tissue as well [ 33 ]. The study of the responses of this type of cells is therefore relevant in order to understand the effects of modulating agents on basic cellular biology in the wound healing process.…”
Section: Discussionmentioning
confidence: 99%
“…Adjuvant signatures were driven by TLRs, cytoplasmic RNA and DNA sensors and the inflammasome, with neutrophils potentially also contributing (Stephen et al ., 2017). By day 7 vaccine transcripts and neutrophils were largely absent, and inflammation was abating, with the presence of what appeared to be tissue repair-associated eosinophils (Coden et al ., 2020; Heredia et al ., 2013; Lloyd et al ., 2018; Toor, 2019; Weller et al ., 2017). Although a previous live-attenuated CHIKV vaccine was associated with some arthropathy (Edelman et al ., 2000), no compelling arthritic signature was evident after SCV vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…Eosinophils have been reported in pruritic papulovesicular eruptions in a case of generalized vaccinia after smallpox vaccination (Beachkofsky et al ., 2010) and are well described as drivers of allergic diseases such as eosinophilic asthma (Bhalla et al ., 2020; Côté et al ., 2020). However, recently a role for eosinophils in tissue repair and wound healing has emerged (Coden et al ., 2020; Lloyd et al ., 2018), particularly for muscle tissues (Heredia et al ., 2013; Toor, 2019; Weller et al ., 2017). That the eosinophils in these resolving post-vaccination lesions are distinct from inflammatory eosinophils is supported by the absence of IL-5 mRNA expression (S2G Table), with anti-IL-5 therapy used for eosinophilic asthma (Walsh, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Uderhardt et al have demonstrated that eosinophils have the capacity to produce strong endogenous thrombin based on the simultaneous expression of the tissue factor and the provision of a procoagulant phospholipid surface enriched with 12/15-lipoxygenase (12/15-LO) [14,15]. Furthermore, Marx et al have highlighted the role of eosinophils in arterial thrombosis by demonstrating that eosinophil deficiency does not affect the induction time of thrombus formation and arterial occlusion [16].…”
Section: The Unrecognized Role Of Eosinophils In Thrombotic Eventsmentioning
confidence: 99%